Pengaruh Kualitas Audit, dan Voluntary Disclosure terhadap Cost of Equity Capital - Muhammad Aldian; Dewi Prastiwi (Universitas Batanghari, 2023)
This study attempts to investigate how audit quality, business size, and voluntary disclosure influence the cost of equity capital. Uses stock quotes from the Yahoo Finance website from 2018 to 2020 and annual reports from the website IDX (Indonesian Stock Exchange), this kind of study is quantitative in nature. Purposive sampling is the sampling approach used, and provides a sample of 107 business data using secondary data. Data processing using SPSS 24, as well as data analysis techniques in the form of multiple linear regression analysis. According to processing findings in this study, audit quality has an adverse impact on the price of equity capital. The cost of equity capital is not affected by the optional disclosure variables at the same time.